Seasonal variation of hypoxic and hypercarbic ventilatory responses in the lizard Tropidurus torquatus - Longhini, Leonardo S. [UNESP]; Porto, Lays S. [UNESP]; Rocha, Aline C. G. [UNESP]; Bicego, Kenia C. [UNESP]; Klein, Wilfried; Gargaglioni, Luciane H. [UNESP] (Elsevier B.V., 2019)
Carbon dioxide (CO2) and oxygen (O-2) influence the breathing pattern of reptiles, especially when CO2 is in excess or O-2 at low concentrations and the effects of these gases on the respiratory response varies according to the species. In addition to respiratory gases, seasonal changes can also modulate breathing pattern and ventilatory responses to hypoxia and hypercarbia. Therefore, the present study investigated the breathing pattern and ventilatory responses to hypercarbia (5% CO2) and hypoxia (5% O-2) of the Neotropical lizard Tropidurus torquatus over a period of one year, covering all seasons (summer, autumn, winter and spring). Our data suggest that like other ectothermic sauropsids, Tropidurus torquatus possesses distinct ventilatory responses to hypoxia and hypercarbia, being more sensitive to changes in CO2 than in O-2. Additionally, the ventilatory responses to hypoxia were more pronounced during summer and hypercanic and pos-hypercapnic ventilatory response was reduced during spring, suggesting that seasonality modulates the control of ventilation in this species.
Keywords: Squamata; Ventilation; Season; CO2; Chemoreceptor